Oliver Freud and Henny Fuchs Freud papers - Freud, Oliver, 1891-1969.; Freud, Eva Mathilde, 1924-1944.; Freud, Henny Fuchs, 1892-1971.
Correspondence, writings, subject files, photographs, and other papers pertaining chiefly to Sigmund Freud and to the emigration of Freud family members from Austria and Europe during World War II. Includes a transcript of Oliver Freud's recollections of his father (1953); correspondence and other papers of and relating to Oliver and Henny Fuchs Freud's daughter, Eva Mathilde Freud; and legal items and other documents relating to Boas (Boaz) family ancestors of Henny Fuchs Freud. Correspondents include Anna Freud Bernays, Princess Marie Bonaparte, Anna Freud, Ernst L. Freud, Martha Freud, Sigmund Freud, Mathilde Freud Hollitscher, and Marianne Kris.
Oliver Freud, engineer, photographer, and son of Sigmund Freud; Henny Fuchs, artist and wife of Oliver Freud.
Collection material in German, French, and English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Sigmund Freud collection.
Portions of the collection were originally processed as part of the Sigmund Freud Papers from which they have now been transferred.
Keywords: Bernays, Anna Freud, -- 1858-1955 -- Correspondence; Bonaparte, Marie, -- Princess, -- 1882-1962 -- Correspondence; Freud, Anna, -- 1895-1982 -- Correspondence; Freud, Ernst L., -- 1892-1970 -- Correspondence; Freud, Eva Mathilde, -- 1924-1944.; Freud, Martha, -- 1861-1951 -- Correspondence; Freud, Sigmund, -- 1856-1939.; Freud, Sigmund, -- 1856-1939 -- Correspondence; Hollitscher, Mathilde Freud, -- 1887-1978 -- Correspondence; Kris, Marianne, -- 1900-1980 -- Correspondence; Boaz family; Freud family; World War, 1939-1945.; Austria -- Emigration and immigration; Europe -- Emigration and immigration